The reverse logistics process applied to the EPS product (ISOPOR) (Research, Society and Development, 2021)
Reflecting the current environmental context of preservation, and of reducing environmental impacts and that are economically sustainable, the reverse logistics process makes it possible to foster and corroborate with the production systems, helping to return post-consumer products. The reverse logistics of EPS (expanded polystyrene - Styrofoam) is still precarious, as it is not economically attractive to cooperatives and their members, when compared to other recyclable products. However, the debate on the topic and the visualization of the data already obtained are extremely relevant. Through the use of the bibliographic methodology it was made from the survey of theoretical references already analyzed, with all the work presents these results and that there is still a lot to be done with the use of EPS in Brazil.